2021
DOI: 10.1097/mcg.0000000000001490
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Emergency Department Assessment and Multidisciplinary Intervention After Discharge Improve Management of Patients With Inflammatory Bowel Diseases

Abstract: Goal:The aim was to assess proactive specialized inflammatory bowel diseases (IBD) emergency department (ED) consultation and multidisciplinary IBD team (IBD-MDT) intervention on IBD-related patient outcomes after discharge.Background: Despite advances in patient care, IBD-related ED visits have increased and substantially contribute to the IBD burden.Methods: Consecutive patients with IBD (below 50 y) who visited the ED during November 2017 to April 2018 (intervention group) were compared with patients with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…It is also not unlikely that the close contact of these patients with our ancillary team members who provided guidance, education, and accessibility impacted response and remission rates. We and others have already shown that an MDT approach and improved accessibility to medical consults benefit decision-making, patients’ quality of care, and rates of hospitalizations 27–30 ; however, our current results suggest that the MDT approach possibly improves disease outcomes.…”
Section: Discussioncontrasting
confidence: 74%
“…It is also not unlikely that the close contact of these patients with our ancillary team members who provided guidance, education, and accessibility impacted response and remission rates. We and others have already shown that an MDT approach and improved accessibility to medical consults benefit decision-making, patients’ quality of care, and rates of hospitalizations 27–30 ; however, our current results suggest that the MDT approach possibly improves disease outcomes.…”
Section: Discussioncontrasting
confidence: 74%
“… 6 , 7 Multidisciplinary team (MDT) clinics can pull together interdisciplinary providers around the IBD patients’ population and improve the quality of care, patient satisfaction, and possibly, outcomes. 8 11 However, outcome data from such an approach in the context of dermatological complications in IBD is lacking. Appreciating the MDT clinics’ advantages, during 2018, we founded an integrated IBD-dermatology (IBD-DERMA) clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Interdisciplinary and multidisciplinary approaches to the identification and treatment of malnutrition can reduce hospital length of stay and improve patient outcomes 8 . For example, an IBD multidisciplinary care approach upon presentation to hospital and post‐discharge reduced hospital readmissions 9 . Nutritional risk screening in both the inpatient and outpatient setting 10 is needed.…”
mentioning
confidence: 99%
“…8 For example, an IBD multidisciplinary care approach upon presentation to hospital and postdischarge reduced hospital readmissions. 9 Nutritional risk screening in both the inpatient and outpatient setting 10 is needed. An advantage of outpatient screening is that it enables earlier patient access to dietitians with IBD expertise.…”
mentioning
confidence: 99%